2021
DOI: 10.1097/iop.0000000000001852
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in Oculoplastics: The Real-Life Application of Video Consultation Clinics

Abstract: Purpose: Our oculoplastic service piloted a new video consultation (VC) clinic in response to the COVID-19 pandemic. Data were collected to determine whether specific patients are better suited to VC, and to quantify the true benefit of VC in patients that successfully attended. Methods: Data were collected prospectively on predetermined data collection forms, including consultation duration, diagnosis, management plan, and issues that arose. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…Our findings were largely consistent with the limited literature on telemedicine use for oculoplastic surgery that has mostly focused on settings outside the United States and singleinstitution reports. [6][7][8][9]11 A descriptive, international survey including a smaller number of oculoplastic surgeons reported similarly high rates of telemedicine use (71%, n = 50) during the COVID-19 pandemic, as well as a similar proportion reporting that they expected to use telemedicine more postpandemic (57%, n = 40). Our study adds important additional information regarding the frequency of telemedicine use relative to oculoplastic surgeons' practice characteristics and data on the categories of visit type, as well as specific clinical indications evaluated.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our findings were largely consistent with the limited literature on telemedicine use for oculoplastic surgery that has mostly focused on settings outside the United States and singleinstitution reports. [6][7][8][9]11 A descriptive, international survey including a smaller number of oculoplastic surgeons reported similarly high rates of telemedicine use (71%, n = 50) during the COVID-19 pandemic, as well as a similar proportion reporting that they expected to use telemedicine more postpandemic (57%, n = 40). Our study adds important additional information regarding the frequency of telemedicine use relative to oculoplastic surgeons' practice characteristics and data on the categories of visit type, as well as specific clinical indications evaluated.…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with other recent reports from single institutions, oculoplastic surgeons in our study reported providing a broad range of telemedicine care during the COVID-19 pandemic, including for new and returning patients, post-and preoperative evaluations, as well as both functional and cosmetic consultations. [6][7][8] One British study suggested that eyelid lesions were among the least well suited for evaluation using telemedicine. However, the majority of our respondents did report using telemedicine to evaluate eyelid lesions (68%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…using a smartphone or webcam). Indeed, it is estimated that almost 40% of new oculoplastic patient encounters and 60% of follow up appointments might be suitable for remote video consultation [ 4 ]. Conducted during the height of the pandemic’s first wave, nationwide surveys of oculoplastic surgeons in the UK and the USA demonstrated that 86.6–88.8% of respondents were incorporating telemedicine into their routine clinical practice [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The feedback was encouraging. Increasing age did not appear to be a factor in successful Oculoplastic VCs from a study of 187 patients [ 4 ]. Our experience reflected this; the ubiquity of devices supporting this platform possibly contributes.…”
mentioning
confidence: 99%